UJI EFEKTIVITAS BERBAGAI BAHAN TUMBUHAN DENGAN POTENSI PESTISIDA NABATI TERHADAP PERKEMBANGAN HAMA WALANG SANGIT (Leptocorisa acuta thunb) - Zaedar Dg Masese; Herwin Yatim; Firdas (Fakultas Pertanian Universitas Tompotika Luwuk, 2023)
Walang sangit (Leptocorisa acuta thumb) is found in rice plants from flowering to harvest. These insects eat rice grains that are developing which have the potential to cause losses both in terms of quality and quantity. Synthetic pesticides are the main alternative for controlling walang sangit because they offer convenience and provide significant results on production per hectare. There have been many reports of the toxicity of synthetic pesticides which have negative effects including contamination of water and soil resources, loss of natural enemies of pests and insect pollinators which disrupt ecosystem functions. Utilization of plant materials with the potential for botanical pesticides is a safe control alternative for the environment and living things. The aim of the research was to determine the effectiveness of various plant materials with the potential of vegetable pesticides (extracts of maja fruit, sirsak leaves and lemon grass) against the activity of the walang sangit pest (L.acuta thumb) and to obtain plant materials with the best potential of vegetable pesticides. The study was carried out using a randomized block design consisting of 4 treatments (water, maja fruit extract, sirsak leaf extract and lemongrass extract ) with a concentration of 30% for each treatment which was repeated 3 times, so there were 12 experimental plots. Treatment P1 (maja fruit extract) was a treatment capable of suppressing the highest attacks of walang sangit with an average attack intensity of 19.44% and the lowest was treatment P0 (control) with an average attack intensity of 85.33%. The results of the 5% BNT test showed no significant difference between treatments P1, P2 and P3, but significantly different from treatment P0 in terms of controlling the locust pest (L.acuta thumb).